METHOD OF ESTIMATION OF MORTALITY RATES FROM LENGTH SAMPLES - Srinath, M; Alagaraja, K (Indian Journal of Fisheries, 2011)
Taking the probable distribution of age of fish as given by Ssentango and;Larkin (1973), and considering the size distribution as available from the d' towithout taking recourse to the assumption of Marten (1978), a model is dtevelopsdto get an estimate of 'Z'. A table is appended to facilitate the estimation